Measuring microfinance impact: A practitioner perspective and working methodology - Benedetta Ferraro; Giampietro Pizzo; Katia Raguzzoni; Matteo Solivo (European Investment Fund (EIF), 2020)
This paper introduces the concepts of impact,impact analysis/assessment and management, outlining the differences between assessment and evaluation, and highlighting their growing importance among the international and European communities.The second part presents underlying reasons for undertaking this research, introducing the methodology designed and adopted by Microfinanza which relies on indicators concerning the three dimensions, i.e. economic, social and environmental.Thirdly, two case studies are presented in order to better explain and practically implement the theoretical framework prefaced in the first part. They are not real-life cases, but they do show how the set of indicators should be applied in two different scenarios. One represents its adoption by a Microfinance Institution (MFI), presenting the impact assessment on financial supply side which aims at understanding how financial institutions could apply this aspect into their daily work. The second one, which is an impact assessment of a financial education activity, displays how the set of indicators could be used for evaluating impact assessment of specific activities.Lastly, the paper outlines the importance of impact assessment and the future steps, underscoring the growing importance of this practice at different levels and for different stakeholders.
Keywords: 330; Mikrofinanzierung; Stakeholder; Wirkungsanalyse; Bewertung